Detection of Diverse N-Acyl-Homoserine Lactones in Vibrio alginolyticus and Regulation of Biofilm Formation by N-(3-Oxodecanoyl) Homoserine Lactone In vitro - Liu, Jianfei; Fu, Kaifei; Wang, Yuxiao; Wu, Chenglin; Li, Fei; Shi, Lei; Ge, Yinlin; Zhou, Lijun (Frontiers in Microbiology, 2017)
Quorum sensing (QS) is a cell-to-cell communication system based on the exchange of small intercellular signal molecules, such as N-Acyl homoserine lactones (AHLs), which act as cell-density mediators of QS gene expression, and are highly variable both in types and amounts in most Gram-negative Proteobacteria. Understanding the regulation of AHLs may contribute to the elucidation of cell density-dependent phenomena, such as biofilm formation. Vibrio alginolyticus is among the most frequently observed marine opportunistic Vibrio pathogens. However, AHL production of this species and its effects on biofilm formation remain to be understood. Here, our study reported the diverse AHL profiles of 47 marine-isolated V. alginolyticus strains and the effects of exogenous 3-oxo-C10-HSL on biofilm formation under different temperature conditions (16 °C and 28 °C). A total of 11 detected AHLs were produced by the isolates, of which 3-OH-C4-HSL, 3-oxo-C10-HSL and 3-oxo-C14-HSL comprised the largest proportions. We also observed that moderate levels of exogenous 3-oxo-C10-HSL (10 and 20 μM) could induce or enhance biofilm formation and alter its structure, while high levels (40 and 100 μM) did not significantly improve and even inhibited biofilm formation in V. alginolyticus. Further, regulation by exogenous 3-oxo-C10-HSL was both concentration- and temperature-dependent in V. alginolyticus.